Epigenetic Regulation of the N-Terminal Truncated Isoform of Matrix Metalloproteinase-2 (NTT-MMP-2) and Its Presence in Renal and Cardiac Diseases - Cruz, Juliana de Oliveira; Silva, Alessandra O.; Ribeiro, Jessyca M.; Luizon, Marcelo R.; Ceron, Carla S. (Frontiers in Genetics, 2021)
Several clinical and experimental studies have documented a compelling and critical role for the full-length matrix metalloproteinase-2 (FL-MMP-2) in ischemic renal injury, progressive renal fibrosis and diabetic nephropathy. Recently, a novel N-terminal truncated isoform of MMP-2 (NTT-MMP-2) was discovered, which is induced by hypoxia and oxidative stress by the activation of a latent promoter located in the first intron of the MMP2 gene. This NTT-MMP-2 isoform is enzymatically active, but remains intracellular in the mitochondria. In this perspective article, we first present the findings about the discovery of the NTT-MMP-2 isoform, and its functional and structural differences as compared to the FL-MMP-2 isoform. Based on publicly available epigenomics data from the Encyclopedia of DNA Elements (ENCODE) project, we provide insights into the epigenetic regulation of the latent promoter located in the first intron of MMP2 gene, which support the activation of the NTT-MMP-2 isoform. We then focus on its functional assessment by covering the alterations found in the kidney of transgenic mice expressing the NTT-MMP-2 isoform. Next, we highlight recent findings regarding the presence of the NTT-MMP-2 in renal dysfunction, kidney and cardiac diseases, including damage observed in aging, acute ischemia-reperfusion injury, chronic kidney disease, diabetic nephropathy, human renal transplants with delayed graft function. Finally, we briefly discuss how our insights may guide further experimental and clinical studies that are needed to elucidate the underlying mechanisms and the role of the NTT-MMP-2 isoform in renal dysfunction, which may help to stablish it as a potential therapeutic target in kidney diseases.